Fundoscopy made easy - Ghosh, Sujoy (Churchill Livingstone/Elsevier, 2010)
Suitable for the medical students and junior doctors, this title covers the basic principles of fundoscopy. It also covers the common conditions likely to be encountered and examined in the MRCP and MRCGP examinations.